STUDY OF FACTORS AFFECTING COMMUNITY INTEREST IN USING TRANSPORTATION CV. MANDIRI RAYA TRAVEL - Didis; Whendy Trissan (Jurusan Pendidikan Teknologi Dan Kejuruan, 2022)
This research was motivated by the development of the City of Palangka Raya which has caused a fairly basic change, where the City of Palangka Raya apart from being a destination for students to seek knowledge is also known to be a place for people from various regions to find work, this has resulted in the city which is known as a beautiful city, is in the spotlight for researchers to examine social problems related to the diversity of the surrounding community. One of them is the existence of a CV. Mandiri Raya Travel in the city of Palangka Raya which is able to make people more interested in using it. The population in this study are people who use CV. Mandiri Raya Travel transportation. The samples taken were 100 people. The data analysis method used in this study is Multiple Linear Regression Analysis, where previously the validity, reliability and classical assumptions were tested. The results of this study indicate that the physical condition of the Travel Fleet has a positive and significant influence on people's interest in using Mandiri Raya Travel, the service has a positive and significant influence on people's interest in using Mandiri Raya Travel, and ticket prices/costs also have a positive and significant influence on public interest. using Mandiri Raya Travel